Planning Management of The Language section in Imporving The Skills Arabic Language of Santriwati at Boarding School An-Nur Tangkit Sungai Galam - Nurhikmah Nurhikmah; Eva Iryani; Sobri Sobri (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe and find out how to apply the planning management process in the language department and the applied strategies and find out many factors that are an obstacle in increasing the Arabic language skills of students at boarding School An-nur tangkit Sungai Gelam, Data research was obtained through observation, interviews and documentation. The type used by the researcher in this study is qualitative research with a descriptive approach. The sources of the researcher's data are the teacher of language department, the language department, as well as the female students. In an effort to upgrade the Arabic language skills of female students, there is a language department organization that supports the achievement of the expected objectives of good management in the process work of program. The results of this study are the process by which the language department program is run in the dormitory, which includes the strategic planning process language department is 1)formulate of goals 2)preparation of work programs, and operational planning in the implemented strategy language department in improving and supporting Arabic language skills which includes, 1) implementation of work programs 2) evaluation of work programs. The factors and solutions that cause female students not to use the Arabic language around Boarding School An-Nur Tangkit Sungai Gelam. From this research, there are also implications for those involved and responsible for the management of the language department program.